Study of the Efficacy and Safety of Contact Lens Used in Trabeculectomy - Bin Li; Miaomiao Zhang; Zhen Yang (Journal of Ophthalmology)
Purpose. To investigate the efficacy and safety of soft bandage contact lens used in trabeculectomy. Methods. This was a prospective, randomized study which enrolled 200 glaucoma patients (200 eyes). Patients were randomized into Group 1, using contact lens after trabeculectomy, and Group 2, without contact lens. The primary outcome measurement was the comparison of success rates at 12 months after surgery. Qualified surgical success was defined as a postoperative intraocular pressure (IOP) value of 6–21 mmHg with or without topical antiglaucoma medication use at the last follow-up visit. Complete success was defined as the IOP between 6 and 21 mmHg without any antiglaucoma medication at the last follow-up visit. Postoperative data included IOP values, best-corrected visual acuity (BCVA), number of antiglaucoma medications, complications related to surgery, and bleb characteristics. Results. There were statistically significant differences between Groups 1 and 2 in mean IOP values at 3, 6, and 12 months after surgery (P<0.05). The 12-month life table rates for qualified surgical success were 94.7% and 86.3% in Groups 1 and 2, respectively (P=0.045). The 12-month life table rates for complete surgical success were 89.6% and 80.0% in Groups 1 and 2, respectively (P=0.042). At 12 months after surgery, the mean numbers of antiglaucoma medications were 0.3 ± 0.4 and 0.5 ± 0.6, respectively. (P=0.001). At the 12-month visit, the maximal bleb area was significantly different between groups (P=0.044), with Group 1 exhibiting a more diffused bleb area. Encysted blebs were observed in 7 (7%) eyes in Group 1 and 17 (17%) eyes in Group 2, with statistically significant differences (P=0.030). The 12-month life table rates for qualified surgical success were 94.7% (91 eyes) and 86.3% (82 eyes) in Groups 1 and 2, respectively (P=0.045). Conclusions. Bandage contact lens is a safe and effective device after fornix-based trabeculectomy.